Analysis of Regional Expenditure in the Government for the 2020 Financial Year - Dyah Mutiarin; Misran Misran; Dicky Izmi Syahputra (Jurnal Ilmiah Manajemen dan Bisnis, 2023)
This study aims to find out the analysis of local government spending in DKI Jakarta Special Region of Yogyakarta, Banda Aceh City, Papua, West Papua for the 2020 Fiscal Year in managing the 2018-2020 regional budget. This research is descriptive. The results of the study show that the spending variance of the Regional Government Expenditures (DKI Jakarta, DIY, Banda Aceh City, Papua, and West Papua) in 2018-2020 is an average of 25.5% -27.7% included in the favorable category variance because the realization of expenditure does not exceed the set budget. Furthermore, from the Harmony Ratio, most regional expenditures are allocated for Operational Expenditures. The average operating expenditure in 2018-2020 is 33.35%, while capital expenditure is 40.16%. The average is taken from the percentage of the five regional governments, and the Regional Expenditure Efficiency Ratio shows that the realization of the expenditure budget never exceeds the budget. The average efficiency ratio is 2018-2020 is 80.88%. This shows that the five regional governments are pretty efficient in making savings or spending efficiency.